(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2020)
This article aims to show possibilities of readings about the actuality of Schopenhauer’s work with regard to the third generation of Human Rights, especially the right to a preserved environment. It was based on the critical reading of the published and unpublished texts by the philosopher Arthur Schopenhauer (1788-1860), in particular his texts about Ethics.